Transcriptional regulation in Drosophila during heat shock: a nuclear run-on analysis. - Vazquez, J.; Pauli, D.; Tissieres, J. (Chromosoma, 1993)
We used a nuclear run-on assay as a novel approach to study the changes in transcriptional activity that take place in Drosophila melanogaster during heat shock. In response to a rapid temperature upshift, total transcriptional activity in cultured KC161 cells decreased proportionally to the severity of the shock. After extended stress at 37 degrees C (15 min or more), transcription was severely reduced, and at 39 degrees C most transcription was instantaneously arrested. However, strikingly different responses were observed for individual genes. Transcription of histone H1 genes was severely inhibited even under mild heat shock conditions. Transcription of the actin 5C gene decreased progressively with increasing temperature, while transcription of the core histone genes or of the heat shock cognate genes was repressed only under severe heat shock conditions. Transcriptional activation of the D. melanogaster heat shock genes was also investigated. In unshocked cells, hsp84 was moderately transcribed, while transcriptional activity at the other protein-coding heat shock genes was undetectable (less than 0.2 polymerases per gene). Engaged but paused RNA polymerase molecules were found at the hsp70 and hsp26 genes, but not at the other heat shock genes. The rates of transcription increased with increasing temperature with a peak of expression at around 35 degrees C. At 37 degrees C, induction was less efficient, and no induction was achieved after a rapid shift to 39 degrees C. Increased transcription of the heat shock genes was observed within 1-2 min of heat shock, and maximal rates were reached within 2-5 min. Despite very similar profiles of response, different heat shock genes were transcribed at strikingly different rates, which varied over a 20-fold range. The noncoding heat shock locus 93D was transcribed at a very high rate under non-heat shock conditions, and showed a transcriptional response to elevated temperatures different from that of protein-coding heat shock genes. An estimation of the absolute rates of transcription at different temperatures was obtained.